TINDAK TUTUR DI DALAM KARIKATUR â€œTAN BAROâ€ PADA SURAT KABAR HARIAN SINGGALANG - Rianti, Nofrika; Juita, Novia; Manaf, Ngusman Abdul (Universitas Negeri Padang, 2017)
This article was written to describe (1) the type of speech act illocutionary in caricature Tan Baro on Daily newspaper Singgalang, (2) types of strategies are spoken caricature Tan Baro on Daily newspaper Singgalang, and (3) the context of the use of strategies recalled in caricature Tan Baro on Daily newspaper Singgalang. This research data is a caricature figure of speech that number Tan Baro 75 utterances of 24 caricature used source of research data are Singgalang Daily newspaper published on Sunday. Data retrieved by collecting all the utterances in caricature Tan Baro on Singgalang Daily newspaper. Analyzing data this studi by transcribing the data, identify, classify, and concludes the description of the data by type of illocutionary speech act, type of strategy speak, and context of use strategies narrate. The research findings are, (1) the type of speech act illocutionary the most widely used is the speech act is representative, (2) type of strategy speak the most widely used is bald on record with the preamble of politeness, and (3) context of use strategy tells consists of, (a) in the context of the speaker acts said to those who more older or higher status and are already familiar tends to use the strategy speak frankly with strings attached politeness positive, (b) in the context of the speaker acts said to the younger people and already familiar tends to use the bald on record strategy.Â Keywords: speech act, illocutionary, caricature, Tan Baro, newspaper, Singgalang Daily.